Managing multinational teams global perspectives - Shapiro, Debra L.; Von Glinow, Mary Ann Young, 1949-; Cheng, Joseph L. C. 1952- (Elsevier, 2005)
Two recent developments from globalization have fundamentally altered the nature of work organizations: the workforce has become increasingly diverse in national and cultural origins, and work assignments are increasingly performed by teams consisting of members located in different countries. Together, these changes have resulted in employees increasingly finding themselves working in culturally diverse, geographical dispersed, multinational teams. Yet, relatively little scholarship has been done to study the dynamics of such teams and how they can be better managed. The current volume presents cutting-edge theorizing and research from a multidisciplinary (e.g., psychology-, communications/technology-, organizational behavior-, and strategy-oriented) group of scholars who have been active in studying multinational teams in a global context. This book is divided into three parts.-The first includes four chapters focusing on culture and other intra-group factors that affect the effective functioning of multinational teams. The second includes five chapters that examine the effect of technology and other external influences on team processes and outcomes. The third part includes four chapters dealing with leadership and management issues. The two final chapters were written by authors who have been actively involved as organizers of multi-country academic research teams whose life spans many years and continues today. Cumulatively, this books chapters provide management scholars a diversity of theoretical and methodological perspectives, at many levels of analysis, and include insights borne from the authors observation-based and/or living-based experience with the culturally-challenging issues they discuss.-Additionally, these chapters also provide practicing managers useful ideas on both intra- and external-group dynamics that help increase their understanding about the effective functioning of multinational teams. As a result, this book offers both breadth and depth on the topic of managing multinational teams in a global context that promise to make its contents of interest to many audiences.
Keywords: Teams in the workplace.; International business enterprises -- Management.; Diversity in the workplace.; Leadership.; elektronické knihy; electronic books